Quantifying human genome parameters in aging - V. P. Volobaev; S. S. Kunizheva; L. I. Uralsky; D. A. Kupriyanova; E. I. Rogaev (Вавиловский журнал генетики и селекции)
Healthy human longevity is a global goal of the world health system. Determining the causes and processes influencing human longevity is the primary fundamental goal facing the scientific community. Currently, the main efforts of the scientific community are aimed at identifying the qualitative characteristics of the genome that determine the trait. At the same time, when evaluating qualitative characteristics, there are many challenges that make it difficult to establish associations. Quantitative traits are burdened with such problems to a lesser extent, but they are largely overlooked in current genomic studies of aging and longevity. Although there is a wide repertoire of quantitative trait analyses based on genomic data, most opportunities are ignored by authors, which, along with the inaccessibility of published data, leads to the loss of this important information. This review focuses on describing quantitative traits important for understanding aging and necessary for analysis in further genomic studies, and recommends the inclusion of the described traits in the analysis. The review considers the relationship between quantitative characteristics of the mitochondrial genome and aging, longevity, and age-related neurodegenerative diseases, such as the frequency of extensive mitochondrial DNA (mtDNA) deletions, mtDNA half-life, the frequency of A>G replacements in the mtDNA heavy chain, the number of mtDNA copies; special attention is paid to the mtDNA methylation sign. A separate section of this review is devoted to the correlation of telomere length parameters with age, as well as the association of telomere length with the amount of mitochondrial DNA. In addition, we consider such a quantitative feature as the rate of accumulation of somatic mutations with aging in relation to the lifespan of living organisms. In general, it may be noted that there are quite serious reasons to suppose that various quantitative characteristics of the genome may be directly or indirectly associated with certain aspects of aging and longevity. At the same time, the available data are clearly insufficient for definitive conclusions and the determination of causal relationships.